A study on understanding potential users' intention to use micro-mobility vehicles: E-scooter systems in İstanbul - Kaplan, Semanur (Graduate School, 2024)
The word 'Technology' is defined by the Turkish Language Association (TDK); It is defined as all the tools and related information that people have developed to control and change their material environment. When we examine it in this context, we can consider every product designed and made available to people as a technology. Acceptance of these new products by individuals and understanding their usage intentions will ensure both the development of technology and the success of the products. Understanding whether a product will be accepted by potential users and predicting users' future usage intentions with a user-centered design approach is very important in terms of creating more successful and profitable products in the market. UTAUT2 model created to understand users' motivations for using the product; It is examined in the context of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, perceived risk, habit, behavioural intention and usage behaviours. With this approach, it is aimed to reveal potential users' intentions to use the product in the future and their reasons for choosing or not choosing the product. Considering the main aim of manufacturers to deliver their products to as many users as possible, it is very important to understand the target audience's perception of the products and their usage intentions in order to produce products that have an important place in the market. In this context, the mission of industrial designers is; The task of designing products acceptable to target users is added. Within the scope of this research, a literature review was conducted on technology acceptance models, urban transportation and shared micro-mobility systems. Urban transportation and product service systems are examined in the context of shared micro-mobility vehicles. Shared micro-mobility systems offer innovative solutions that transform urban transportation, making it more sustainable, accessible and economical. It will have an important place in urban transportation in the future with its features such as reducing traffic congestion, being environmentally friendly, providing accessibility to other public transportation networks, being economical and being healthier because it encourages physical activity. In this context, within the scope of this thesis, a research was conducted on potential users using the 'Unified theory of acceptance and use of technology (UATUT2)' in order to analyze the factors affecting the technology acceptance of shared micro-mobility vehicles in urban transportation. Data collection stages are as follows; It consists of semi-structured interviews, field stud and surveys. The research results were evaluated together with the findings. Based on the findings obtained within the scope of the research, a comprehensive insight was obtained about the intentions of potential users to use shared micro-mobility systems in the future and development suggestions were presented for industrial designers to develop e-scooters.
Potansiyel kullanıcıların mikromobilite araçlarını kullanma niyetlerini anlama üzerine bir çalışma: İstanbul'da e-scooter sistemleri
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: micro-mobility vehicles; mikromobilite araçlar; e-scooters; e-scooter